2018
DOI: 10.1021/acscatal.8b00330
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Pt/CeO2 Interface by in Situ Variation of the Pt Particle Size

Abstract: Pt-CeO2-Al2O3 catalysts play an important role in diesel oxidation and three-way catalysis. In this study, the fast structural dynamics of both platinum and ceria in a 1 wt %Pt/5 wt %CeO2-Al2O3 catalyst prepared by flame spray pyrolysis have been systematically investigated under reducing and oxidizing conditions to elucidate the role of the Pt–CeO2 interface for CO oxidation and fast oxygen storage/release of ceria. The catalyst showed enhanced catalytic activity, particularly after application of a reducing/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
166
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(179 citation statements)
references
References 51 publications
10
166
1
2
Order By: Relevance
“…Chemie size and spacing can also be tuned after synthesis by redox cycling, using ap re-selected temperature and reduction gas, for example,H 2 or CO. [60] This is in line with an early Tu rbo-XAS study of Nagai et al [61] showing temperature-dependent in situ redispersion in Pt/CeZrYO x automotive catalysts upon redox cycling.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…Chemie size and spacing can also be tuned after synthesis by redox cycling, using ap re-selected temperature and reduction gas, for example,H 2 or CO. [60] This is in line with an early Tu rbo-XAS study of Nagai et al [61] showing temperature-dependent in situ redispersion in Pt/CeZrYO x automotive catalysts upon redox cycling.…”
Section: Methodssupporting
confidence: 79%
“…[59] By combining O 2 and N 2 plasma (N 2 *) Pt ALD,Dendooven et al [56] independently tuned the Pt NP size and center-to-center distance on ap lanar support (Figure 5a). GISAXS showed that after depositing as elected number of Pt NPs by MeCpPtMe 3 -O 2 ALD,subsequent MeCpPtMe 3 -N 2 *ALD only increased their size,w hile keeping the center-to-center distance constant: i) the constant q y -values of the lobe maxima evidence the constant NP spacing, while ii)the shift of the lobe minima in q y and q z to lower values and the appearance of as econdary lobe is characteristic for an increasing NP width and height, respectively.N otably,aQXAS study showed that the Pt NP size and spacing can also be tuned after synthesis by redox cycling, using ap re-selected temperature and reduction gas, for example,H 2 or CO. [60] This is in line with an early Tu rbo-XAS study of Nagai et al [61] showing temperature-dependent in situ redispersion in Pt/CeZrYO x automotive catalysts upon redox cycling.…”
Section: Birth Of Ananoparticlesupporting
confidence: 79%
“…Ganzler et al. reported that small Pt clusters supported on CeO 2 are much more active than atomically dispersed Pt and a size of ∼1.4 nm was reported to be optimal . The origin of the high CO oxidation activity on ceria supported Pt nanoparticles was proposed to be due to highly active sites at the Pt−CeO 2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of such tandem catalytic systems requires advanced synthetic methodologies for both the ceria preparation and the active component deposition. The scalable methods of preparation of CeO 2 supports vary from the cerium salts solution hydrolysis to the flame spray pyrolysis . Among these methods the simplest and most straightforward one is the thermal decomposition of cerium salts, such as Ce(NO 3 ) 3 ⋅ 6H 2 O, Ce 2 (C 2 O 4 ) 3 , (NH 4 ) 2 [Ce(NO 3 ) 6 ], and Ce 2 (CO 3 ) 2 O ⋅ H 2 O .…”
Section: Introductionmentioning
confidence: 99%